2017
DOI: 10.1371/journal.pone.0177477
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of patients’ activities and interactions in a stroke unit before and after reconstruction—The significance of the built environment

Abstract: Early mobilization and rehabilitation, multidisciplinary stroke expertise and comprehensive therapies are fundamental in a stroke unit. To achieve effective and safe stroke care, the physical environment in modern stroke units should facilitate the delivery of evidence-based care. Therefore, the purpose of this study was to explore patients’ activities and interactions in a stroke unit before the reconstruction of the physical environment, while in a temporary location and after reconstruction. This case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…High‐quality care that is safe, efficient and person‐centred requires a high standard for the physical environment (architecture or built environment) (Anåker, Heylighen, Nordin, & Elf, ; Clancy, ; Sadler et al., ). A recent study on a new stroke unit showed that the environment negatively affected patients’ activity levels (Anåker, von Koch, Sjostrand, Bernhardt, & Elf, ). However, studies on how the environment has an impact on health, rehabilitation and stroke care are still scarce; thus, the environment and its importance are not addressed in Swedish or European stroke guidelines (Ringelstein et al., ; Socialstyrelsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…High‐quality care that is safe, efficient and person‐centred requires a high standard for the physical environment (architecture or built environment) (Anåker, Heylighen, Nordin, & Elf, ; Clancy, ; Sadler et al., ). A recent study on a new stroke unit showed that the environment negatively affected patients’ activity levels (Anåker, von Koch, Sjostrand, Bernhardt, & Elf, ). However, studies on how the environment has an impact on health, rehabilitation and stroke care are still scarce; thus, the environment and its importance are not addressed in Swedish or European stroke guidelines (Ringelstein et al., ; Socialstyrelsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…This framework supports that physical design features may need to be different for specific patient groups. A recent study observed stroke survivors in a Swedish acute stroke unit pre and post rebuilding of the unit, and highlighted how location of the communal area and bed lay out (single vs. multi-room) influenced activity levels of stroke survivors, and their ability to optimally engage with the environment (Anaker et al, 2017). Findings indicated that in the new acute stroke unit, stroke survivors spent more time alone, in their rooms, and were less active compared with stroke survivors who recovered in the original 'old' unit (Anaker et al, 2017).…”
Section: Effect Of the Physical Built Environment On Activitymentioning
confidence: 99%
“…A recent study observed stroke survivors in a Swedish acute stroke unit pre and post rebuilding of the unit, and highlighted how location of the communal area and bed lay out (single vs. multi-room) influenced activity levels of stroke survivors, and their ability to optimally engage with the environment (Anaker et al, 2017). Findings indicated that in the new acute stroke unit, stroke survivors spent more time alone, in their rooms, and were less active compared with stroke survivors who recovered in the original 'old' unit (Anaker et al, 2017). While there is a push towards single bed spaces for reasons such as infection control and privacy, the possible impact of single rooms on stroke recovery, activity levels and interaction with others needs to be seriously considered (Pennington & Isles, 2013).…”
Section: Effect Of the Physical Built Environment On Activitymentioning
confidence: 99%
See 2 more Smart Citations